Traditional Uses of Plants in the Tolfa–Cerite–Manziate Area (Central Italy) - Paolo Maria Guarrera; Valentina Savo; Giulia Caneva (Ethnobiology Letters, 2015)
Traditional knowledge of local plant uses is rapidly fading away, especially in rural Mediterranean areas. We carried out ethnobotanical research in 2010-2011 in order to investigate the local knowledge of wild plants in the Tolfa–Cerite–Manziate area of Italy (Latium, district of Rome). We carried out a total of 45 semi-structured interviews with farmers, herders, and fishers. Here, a simple diachronic comparison is made between the current study and a previous one conducted in some of the villages of the study area to highlight potential losses of traditional knowledge of local plants. We documented a total of 102 plant species, belonging to 48 families, along with their uses (excluding food uses). We also reported some non-plant based remedies that were primarily used in veterinary medicine. Some plant uses, especially for making handicrafts, have not been reported previously (e.g., those of Celtis australis L. Cannabaceae, Betula pendula Roth Betulaceae). Many plant uses are no longer remembered in the area, which indicates a loss of local ethnobotanical knowledge.